The relationships between social media marketing communications, consumer-based brand equity and consumer response among automotive brands in Malaysia - Adetunji, Raji Ridwan (2018)
Developing and managing brand equity are top priorities for many organizations because brand is one of the most prized assets of organizations. As such, academia continues to exert substantial efforts on understanding the factors that influence the development of Consumer-Based Brand Equity (CBBE) and its consequences. However, researchers have not really focused on measuring CBBE from the context of automotive brands. Also, considering the continuous advent of digital platforms such as social media, the environment of marketing communications is changing, leaving a knowledge gap on how the contents disseminated on social media are enhancing CBBE and consumer response. Relaying on the Consumer Stimulus-Response Model (CSRM), this study examines the relationships between the social media marketing communications, specifically, user-generated type (Social Media Word-of-Mouth) and firm created types (Social Media Advertising, Social Media Promotion and Social Media Interactive Marketing), CBBE and Consumer Response among automotive brands. To validate the scales employed in this study, semi-structured face-to-face interviews was conducted among ten (10) informants and seven (7) experts were recruited to content validate the developed scales before conducting pilot study among 200 respondents. Subsequently, 800 users of four types of automotive brands namely; PROTON, PERODUA, TOYOTA and HONDA were surveyed using a self-administered questionnaire. The data collected was analyzed using SEM. The findings revealed that, Social Media Advertising, Social Media Promotion, Social Media Interactive Marketing and Social Media Word-of-Mouth have significant relationships with the CBBE of automotive brands and consumer response. Furthermore, CBBE demostrates a significant indirect effects on the relationships between social media marketing communications and CBBE. Consequently, this study provide empirical evidence to the CSRM and provide insights for brand managers on how to enhance brand equity of automotive brands through marketing communications disseminated on social media platforms